2010
DOI: 10.1063/1.3280043
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental evidence of enhanced ferromagnetism in Ba and Mn cosubstituted BiFeO3

Abstract: Ba and Mn doped BiFeO3 prepared through the pyrolysis of xerogel precursors are characterized by powder x-ray diffraction, high resolution transmission electron microscopy, superconducting quantum interference device magnetometry, and polarization measurements. Structural studies by x-ray diffraction and transmission electron microscopy show a tetragonal lattice for Ba substituted BiFeO3 and a rhombohedral lattice for Mn substituted BiFeO3. A large ferromagnetic hysteresis loop is observed for Ba doped BiFeO3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 19 publications
6
34
0
Order By: Relevance
“…It is noticed that the simulated XRD pattern agrees well with the measured data with no structural phase transition from rhombohedral to any other phase as it has been reported earlier that Ba and Mn substitution with (x ≤ 0.4) has not affected the crystalline structure of the parent compound BFO, which is important for the FE properties of the compounds [24]. It is worth to comment that Jayakumar and researchers have synthesized compositions by the pyrolysis of xerogel precursors [25]. The powder X-ray diffraction XRD patterns were analyzed by Rietveld refinement of using FULLPROF 2000.…”
Section: Structural Analysissupporting
confidence: 81%
“…It is noticed that the simulated XRD pattern agrees well with the measured data with no structural phase transition from rhombohedral to any other phase as it has been reported earlier that Ba and Mn substitution with (x ≤ 0.4) has not affected the crystalline structure of the parent compound BFO, which is important for the FE properties of the compounds [24]. It is worth to comment that Jayakumar and researchers have synthesized compositions by the pyrolysis of xerogel precursors [25]. The powder X-ray diffraction XRD patterns were analyzed by Rietveld refinement of using FULLPROF 2000.…”
Section: Structural Analysissupporting
confidence: 81%
“…A saturated magnetization of 0.4 emu/ g and remnant magnetization of 0.14 emu/g are observed at 300 K. The magnetic property is enhanced for (Eu, Co)-doped sample. This variation tendency is consistent with the results reported in other kinds of co-doped samples [14,15]. As to the origin of this enhancement of ferromagnetism, it is necessary to look into the local atomic and electronic structure of all samples.…”
Section: Resultssupporting
confidence: 88%
“…Cui et al [13] have reported improved ferromagnetic properties of (La, Ti) codoped BiFeO 3 , which is attributed to the tetragonal lattice structure. It is almost same to the (Ba, Mn) codoped sample [14]. For (Eu, Co) codoped samples, there are still very few reports on investigating the magnetization in terms of local atomic structure.…”
Section: Introductionmentioning
confidence: 50%
“…The onset of ferromagnetism in BBFO nanostructures could be attributed to the suppression of spiral spin order and structural distortion by Ba-doping which is quantified as changes in Fe-O-Fe bond angle, φ. [34][35][36] As shown in Table I, φ increase significantly with Ba-doping which is analogous with previous investigation. 37 The change in bond angle modifies the tilting angle of FeO 6 octahedron which might suppress the spiral spin structure and hence outset net magnetization in BBFO nanoparticles.…”
Section: Room Temperature M-h Hysteresis Loops Of Nanocrystalline Bfosupporting
confidence: 78%
“…The observed H c value for 49 nm BBFO sample is in good agreement with some previously published values. 35,36 The coercive field may originate from locking of local moments associated with local distortions in BBFO samples which could be described as ferromagnetic (FM) pinning in antiferromagnetic (AFM) super lattice. 35,36 The association of pinning mechanism with the observed coercive field may be substantiated by the derivative of magnetization (dM/dH) plot as shown in the inset of Fig.…”
Section: -9mentioning
confidence: 99%